Hospital-Based Social Work: Challenges at the Interface between Health and Social Care. (11th December 2018) - Heenan, Deirdre; Birrell, Derek
Abstract: This article analyses the complexity and challenges of hospital-based social work in the rapidly changing and financially driven climate of health and social care. It is based on the findings of an exploratory qualitative study of social work in an acute hospital in Northern Ireland. It considers the intensity and variety of social work practice in this clinical setting and explores the challenges and rewards of inter-professional collaboration. It suggests that hospital-based social workers occupy a unique place at the interface of health and social care, yet relatively little is known about their role and contribution. Whilst these highly skilled professionals play a pivotal part in ensuring the well-being of service users, their traditional roles have become secondary to co-ordinating hospital discharge. It is argued that the focus on avoiding delayed discharges and increasing patient throughput may overshadow their strategic and value-based contributions. Finally, it is clear that inter-professional working can improve health outcomes and facilitate optimum well-being; this study highlights a number of areas of concern for social workers working in these teams.